Review Of Safety Equipment On Ferry Ship KMP. Bontoharu On The Bira – Pamatata Route, South Sulawesi Province - Purboyo, Purboyo; Irwan, Irwan; Taufiqurrahman, Muhammad (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2023)
South Sulawesi is a province of Indonesia that consists of 24 regencies/cities with a total area of 45,764.53 km2. Bulukumba Regency is a regency that is in a strategic area when viewed from the characteristics of the wider area because there is a regional-scale transportation infrastructure, namely the Bira Ferry Port. The Bira Ferry Port is located in Bulukumba Regency which is in the territory of South Sulawesi Province. A very important role is the main crossing port for the distribution of products and the movement of people. The completeness of the number and feasibility of passenger safety equipment on board is an important benchmark in supporting the level of safety. Regulations determined by SOLAS 2014, fading life buoy colors, lifeboats that are not suitable for use, storage locations for life jackets that are difficult to reach and life jackets that are still lacking. The safety equipment on board is a benchmark in supporting the level of safety on board.